1990
DOI: 10.1159/000150140
|View full text |Cite
|
Sign up to set email alerts
|

Cell Activation Signals and the Pathogenesis of Human Cytomegalovirus

Abstract: Cytomegalovirus (CMV) infection induces a series of cellular responses that resemble those observed in cells activated by growth factors or hormones including: hydrolysis of phosphatidylinositol-4,5-bisphosphate; Ca2+ influx and an increase in the cytosolic free [Ca2+]; an increase in Na+ entry; and, increases in cellular levels of cyclic AMP and cyclic GMP. The time courses for some of these responses appear to be markedly protracted relative to those observed for growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 15 publications
1
39
0
Order By: Relevance
“…It is known that, following CMV infection, effector responses such as inositol lipid hydrolysis, kinase activation, and arachidonic acid metabolism are increased within the host cell and are required to direct and control early viral gene expression and DNA replication (47). Here we show that HCMV also induces a strong activation of CRE, at early and late times post infection.…”
Section: Discussionmentioning
confidence: 57%
“…It is known that, following CMV infection, effector responses such as inositol lipid hydrolysis, kinase activation, and arachidonic acid metabolism are increased within the host cell and are required to direct and control early viral gene expression and DNA replication (47). Here we show that HCMV also induces a strong activation of CRE, at early and late times post infection.…”
Section: Discussionmentioning
confidence: 57%
“…This viral US28 may have some propensity to bind fractalkine on target cells (Kledal et al, 1998) and would be inserted into the plasma membrane of the target cell after fusion. Whether this protein is responsible for cellular changes associated with G protein signaling (Albrecht et al, 1990) remains to be established. The possibility that other proteins, including the viral glycoproteins involved in fusion and entry, are located on endocytic membranes also remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…This protein binds with high affinity to several CC-chemokines such as macrophage inflammatory polypeptide (MIP)-1␣, MIP-1␤, monocyte chemotactic protein (MCP)-1, and regulated on activation normal T cell expressed and secreted (RANTES) (Neote et al, 1993;Gao and Murphy, 1994;Kuhn et al, 1995) as well as the CX 3 C-chemokine fractalkine (Kledal et al, 1998). At the cellular level, HCMV infection induces cellular changes, some of which are associated with G-protein signaling (Albrecht et al, 1990). Signal transduction through US28 has been observed as a transient increase in intracellular calcium in response to high CC-chemokine concentrations (Gao and Murphy, 1994;Vieira et al, 1998) and as an activation of the mitogen-activated protein kinase pathway in response to RANTES (Billstrom et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…CMV was shown to affect transmembrane signaling pathways (12)(13)(14) including the cAMP-dependent protein kinase A pathway (15,31). cAMP serves as a multifunctional relay for mitogenic stimuli acting as an intracellular signal for activation of eukaryotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…CMV infection in vitro has been shown to affect cellular activation pathways of human fibroblasts. CMV was reported to induce the hydrolysis of phosphatidyl inositol 4,5 biphosphate (PIP 2 ), Ca 2 ϩ influx, and an increase in intracellular free Ca 2 ϩ , as well as increased cellular levels of cAMP and cGMP (12), and arachidonic acid (AA) metabolism (13,14). More recently, it has been reported that CMV affects transmembrane signaling pathways in CD4-positive T-lymphocytes.…”
Section: Cytomegalovirus (Cmv)mentioning
confidence: 99%